Multibend achromat lattice with four dispersion bumps for sextupole cancellation - Jiajie Tan; Bingfeng Wei; Penghui Yang; Zhenghe Bai; Lin Wang; Jianhua He (Physical Review Accelerators and Beams)
Hybrid multibend achromat (MBA) lattice with a pair of dispersion bumps separated by −I transformation is used in some diffraction-limited storage ring (DLSR) designs, which can obtain relatively large dynamic apertures. However, the −I transformation also largely restricts the horizontal tune of the lattice cell. In this paper, an MBA lattice with four dispersion bumps is proposed, which has relatively good flexibility in adjusting the number of bends in the lattice cell and the lattice cell tunes, while also achieving the effective sextupole cancellation within the lattice arc section. The new lattice can have a larger horizontal cell tune than the hybrid MBA lattice with the same number of bends, which is beneficial for reducing the emittance. In the new lattice, −I transformation is not necessary for the sextupole cancellation between paired bumps, and a general relation of sextupole cancellation is used. Following this lattice concept, a 7BA lattice is preliminarily designed for a 1.5 GeV DLSR. This lattice concept can also be extended to the case of MBA lattice with more bumps.